2019
DOI: 10.1093/mnras/stz3199
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of galaxy formation on matter clustering through a library of simulation power spectra

Abstract: Upcoming weak lensing surveys require a detailed theoretical understanding of the matter power spectrum in order to derive accurate and precise cosmological parameter values. While galaxy formation is known to play an important role, its precise effects are currently unknown. We present a set of 92 matter power spectra from the OWLS, cosmo-OWLS and bahamas simulation suites, including different ΛCDM cosmologies, neutrino masses, subgrid prescriptions and AGN feedback strengths. We conduct a detailed investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
160
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(174 citation statements)
references
References 84 publications
13
160
1
Order By: Relevance
“…However, it has become increasingly evident over the last few years that baryonic processes (which are ignored in gravity-only N -body simulations and associated regression techniques) have a significant effect on current and future weak-lensing observations. Several hydrodynamical simulations which include feedback effects from active galactic nuclei (AGN) and supernova explosions have shown that the clustering signal is affected by 10-30 percent at the nonlinear scales [16][17][18][19][20][21][22][23]. Similar effects have been found using the more analytical and physically intuitive approach of the halo model [24][25][26][27].…”
Section: Introductionmentioning
confidence: 69%
“…However, it has become increasingly evident over the last few years that baryonic processes (which are ignored in gravity-only N -body simulations and associated regression techniques) have a significant effect on current and future weak-lensing observations. Several hydrodynamical simulations which include feedback effects from active galactic nuclei (AGN) and supernova explosions have shown that the clustering signal is affected by 10-30 percent at the nonlinear scales [16][17][18][19][20][21][22][23]. Similar effects have been found using the more analytical and physically intuitive approach of the halo model [24][25][26][27].…”
Section: Introductionmentioning
confidence: 69%
“…In addition, it is well known that baryonic effects on the matter power spectrum are of the order of ∼10-20% and cause a suppression in the power spectrum at k > ∼ 0.1 Mpc −1 h (van Daalen et al 2011;Mummery et al 2017;Schneider et al 2019;van Daalen et al 2020;Debackere et al 2020). The DDE cosmologies considered here produce effects of similar magnitude, although they extend throughout the linear and non-linear regime and should therefore be distinguishable from baryonic effects given a wide enough range of well-sampled k values.…”
Section: Matter Power Spectrummentioning
confidence: 78%
“…This has been shown with respect to the matter power spectrum (e.g. van Daalen et al 2011;Schneider et al 2019;van Daalen et al 2020), the halo mass function (e.g. Sawala et al 2013;Cusworth et al 2014;Velliscig et al 2014), clustering (van Daalen et al 2014, density profiles (e.g.…”
Section: Impact Of Baryons and Its Dependence On Cosmologymentioning
confidence: 89%
See 1 more Smart Citation
“…As already shown in the main text (see Figs. [6][7][8], there is a noticeable gain when adding external data from X-ray gas fractions, i.e when going from the…”
mentioning
confidence: 99%